Moral dilemmas in healthcare during the COVID-19 pandemic: an organizational perspective - Vecchio, Luca P.; Colombo, Monica (Frontiers in Organizational Psychology, 2025)
IntroductionThe COVID-19 pandemic exposed healthcare professionals to unprecedented ethical challenges, forcing them to confront moral dilemmas under conditions of uncertainty, scarcity, and institutional pressure. This study examines these experiences through an organizational lens, emphasizing the interplay between structural constraints, moral distress, and sensemaking.MethodsUsing a qualitative design, 13 physicians and nurses from hospitals in Lombardy (Italy) were interviewed through semi-structured protocols exploring their emotional, ethical, and organizational experiences during the pandemic. Data were analyzed through a hybrid coding framework combining the Moral Distress Model with concepts of organizational sensemaking and ethical suffering.ResultsThe analysis confirmed all categories of moral events identified in the Moral Distress Model and revealed additional cross-cutting themes such as emotional overload, institutional betrayal, and peer solidarity. Participants described a collapse of ethical frameworks and the emergence of “warfare triage,” reshaping professional identity and moral reasoning.DiscussionThe findings reveal how organizational breakdowns transformed moral agency into ethical suffering. Strengthening institutional ethics infrastructures and collective sensemaking processes is essential to support healthcare professionals' moral resilience in future crises.